Brains in Sync: Practical Guideline for Parent–Infant EEG During Natural Interaction - Turk, Elise; Endevelt-Shapira, Yaara; Feldman, Ruth; van den Heuvel, Marion I.; Levy, Jonathan (Frontiers in Psychology, 2022)
Parent-infant EEG is a novel hyperscanning paradigm to measure social interaction simultaneously in the brains of parents and infants. The number of studies using parent-infant dual-EEG as a theoretical framework to measure brain-to-brain synchrony during interaction are rapidly growing, while the method on how to measure this is not yet uniform. While adult dual-EEG methodology is quickly improving, open databases, tutorials, pipelines, and methodological validations for dual-EEG with infants are largely missing. In this practical guide, we provide a step-by-step manual on how to implement and run parent-infant EEG paradigms in a neurodevelopmental laboratory in naturalistic settings (e.g., free interactions). Next, we give insights on the variety of choices that can be made during (pre)processing dual-EEG data, including recommendations on interpersonal neural coupling metrics and interpretations of the results. Moreover, we are providing an exemplar dataset of two mother-infant dyads during free interactions (“free play”) that may serve as practice material. Instead of providing a critical note, we would like to move the field of parent-infant EEG forward and be transparent about the challenges that come along with the exciting opportunity to study the development of our social brain within the naturalistic context of dual-EEG.